2012
DOI: 10.1108/02640471211204060
|View full text |Cite
|
Sign up to set email alerts
|

Virtual references services: defining the criteria and indicators to evaluate them

Abstract: PurposeThis paper aims to analyse the common features of the virtual reference services provided by European and American libraries in order to evaluate the service from the user's perspective, taking into account the potential of Web 2.0 applications.Design/methodology/approachThis research adopts a quantitative approach, to contribute to better understanding of the problems currently facing virtual reference services and offers solutions to them. The study also combines qualitative methodologies.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…While there is a wealth of professional literature about reference competencies, much of this focuses on specific skills or new service models, such as virtual reference (Pinto and Manso 2012), ebooks (Bell 2009), embedded librarians (Hoffman 2011; Kennedy 2011), or roving reference (Gadsby and Qian 2012). Considerably less attention has been paid to the overall context of reference work in academic libraries, or the range of skills staff need to be effective.…”
Section: Related Literaturementioning
confidence: 99%
“…While there is a wealth of professional literature about reference competencies, much of this focuses on specific skills or new service models, such as virtual reference (Pinto and Manso 2012), ebooks (Bell 2009), embedded librarians (Hoffman 2011; Kennedy 2011), or roving reference (Gadsby and Qian 2012). Considerably less attention has been paid to the overall context of reference work in academic libraries, or the range of skills staff need to be effective.…”
Section: Related Literaturementioning
confidence: 99%
“…6 At McGill University Library, there were no immediate concerns with regard to quality of the service. The group also chose not to evaluate individual transcripts for quality because the study would be selective in nature and may not be representative of the overall quality of service provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He found that Web 2.0 is influencing the way in which people learn, access information and communicate with each other. Pinto and Manso (2012) analyzed common features of the virtual reference services provided by European and American libraries to evaluate the service from the user perspective through considering the potential of Web 2.0 applications. The research showed that certain features of virtual reference services which were undervalued or had not attracted research interest required a technological shift in the services provided to users by academic communities involved in that study.…”
Section: Literature Reviewmentioning
confidence: 99%